Due Process of Law in Verification and Validation of Electronic Evidence on The Use of Fake Motor Vehicle Registration Numbers in The Enforcement of Etilang - Farhan Nabil Wijaya; Wibi Saputro; Raden henda; Agus Dimyati (Journal of World Science, 2025)
The implementation of the electronic ticketing system (Electronic Traffic Law Enforcement/ETLE) represents a modernization of traffic law enforcement based on information technology. This study aims to analyze the verification and validation mechanisms of electronic evidence within the ETLE system and assess its compliance with the principles of criminal procedure law, particularly the due process of law, the principle of legal certainty, and the protection of violators' rights. This study employs a normative juridical approach, analyzing laws and regulations and legal doctrine, further strengthened by interview results from Cirebon Resort Police officers. The study's findings indicate that the verification and validation mechanisms for electronic evidence in the ETLE system currently lack standard operating procedures, are conducted entirely internally, and have not been supervised by an independent institution. Furthermore, the use of fake TNKB by perpetrators of violations cannot be effectively detected, leading to errors in identifying legal subjects and potentially infringing upon citizens' constitutional rights. Therefore, the ETLE system necessitates legal and technical reforms, including the establishment of an independent verification agency and strengthened regulations to ensure that electronic evidence can be legally, accurately, and objectively tested. Moreover, bolstering the integration of vehicle data with digital identification systems is crucial to ensure legal certainty and prevent the criminalization of innocent parties.